Performance analysis of DSR protocol on the basis of DSSS rate - Hakak, Saqib Iqbal; Abdul Latif, Suhaimi; Anwar, Farhat; Gilkar, Gulshan; Alam, Mohammed Khorshed (Institute of Electrical and Electronics Engineers Inc., 2014)
MANET or mobile adhoc network is infrastructure less network which does not require any centralized support. Equipped with CSMA/CA (carrier sense multiple access with collision avoidance) transceivers, mobile nodes communicate via radio. As network topology always changes due to mobility of nodes, routing as well as routing protocol selection is quite daunting and challenging in MANET. Direct sequence spread spectrum (DSSS) is a modulation technique used for spreading spectrum of a transmitted signal and is applied at physical layer. Very few studies have focused on effect of DSSS rate on performance of routing protocols. In this paper, the performance analysis of DSR (dynamic source routing) routing protocol which is reactive protocol is done with varying CBR traffic and DSSS rate for important and key network performance metrics which are throughput, end-to-end packet delay and jitter.